مقارنة بين نموذج VAR و ARIMA للتنبؤ بالتضخم في الجزائر: Comparison of the VAR and ARIMA model for inflation prediction in Algeria - بلحاج عمارة شهرزاد (Journal of North African Economies, 2025)
This study aims to predict the inflation index in Algeria during the period from 2021 to 2023 by using statistical data from 1980 to 2021, in addition to macroeconomic indicators for the standard study, which are economic growth, unemployment and the balance of payments. And by using two different models, the vector autoregressive VAR model and the autoregressive and moving average model ARMA, and to achieve the goal for which the prediction process was made, the predictive values of both models were evaluated based on the statistical criteria MAPE, RMSE and MAE to compare between the two models through the values of Errors and prediction accuracy, where the ARIMA model (1,1,4) proved superior to the VAR model.